Pengaruh Diameter Nozzle dan Temperatur Pemanasan Mesin Ekstruder Sampah Plastik Hdpe terhadap Laju Produksi dan Keseragaman Diameter Filamen - Saipul Bahri; Nurlia Pramita Sari; Moh Hartono; Agus Harijono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Plastic waste, particularly High-Density Polyethylene (HDPE), poses a serious threat to the environment due to its extremely long decomposition time. One effective recycling method is the extrusion process, in which process parameters such as nozzle diameter and heating temperature significantly affect the production rate and the quality of the resulting filament. This study aims to analyze the effect of nozzle diameter and heating temperature on the production rate and diameter uniformity of recycled HDPE plastic filament. The method used is an experimental approach with a quantitative design, utilizing a single-screw type extruder machine. The tested parameter variations include two nozzle diameters (1.75 mm and 2.85 mm) and three temperature levels (200°C, 240°C, and 280°C). The results of the analysis, using factorial ANOVA and control charts, show that both parameters significantly influence production performance. The highest production rate, approximately ±1.0 kg/hour, was achieved with the 2.85 mm nozzle and 280°C temperature combination, while the combination of the 1.75 mm nozzle and 200°C temperature produced the most consistent filament diameter and the best quality, with a resulting diameter of 2.84 mm, which is very close to the target of 2.85 mm. Higher temperatures increase flow rate due to decreased viscosity, but also carry the risk of thermal degradation. This study provides practical guidelines for optimizing the HDPE recycling process through extrusion.